An Empirical Note on the Long-Run Effects of Public and Private R&D on TFP - Dierk Herzer (Journal of the Knowledge Economy, 2021)
Several studies have examined the long-run effects of public and private R&D on TFP with mixed results. A common feature of these studies is that they measure public and private R&D activity using perpetual inventory stocks of public and private R&D capital, constructed under the assumption that the prices of GDP, public R&D, and private R&D move identically. This note argues that the results of these studies may be biased if the assumption of identical price movements is violated. The purpose and main contribution of this note is to estimate the long-run elasticities of TFP with respect to public and private R&D using both the stock of public/private R&D capital and an alternative measure of public/private R&D activity: the number of public/private sector researchers. In addition, this study contributes to the literature by developing a simple theoretical model that formalizes the intuition of how public and private R&D affect TFP, and by using both traditional and more recent panel methods. Contrary to previous studies, it is found—using numbers of researchers in the public and private sector—that there is strong evidence both of a significant positive long-run effect of both public and private R&D on TFP and of a greater effect of public R&D than private R&D. Consistent with the mixed evidence reported in the literature, it is also found that the use of public and private R&D stocks yields mixed results regarding the long-run effects of public and private R&D on TFP.
Keywords: O30; O47; O11; 330; Public R&D; Private R&D; Total factor productivity; Panel cointegration